2019
DOI: 10.1021/acs.jced.8b01125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol and Temperature on Partition Coefficients of Ethyl Acetate, Isoamyl Acetate, and Isoamyl Alcohol: Instrumental and Predictive Investigation

Abstract: For alcoholic beverages such as beer, downstream processing for either dealcoholization or off-flavor removal requires both quantitative data and suitable predictive methods. Along with experimental investigations, we use a method initially developed for studying the solubility of gases in two or more miscible liquid solvents to monitor the effect of ethanol on air–water partition coefficients of three major flavors found in beer, namely, isoamyl alcohol, ethyl acetate, and isoamyl acetate. In the ethanol conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The partition coefficient is usually measured for water/air systems (see Supporting Information 2), but dissolved substances such as minerals, sugar and other organics can exert a high influence on KVOC,L/G [7, 19, 4956]. Hence, KVOC,L/G values for a given medium/air system have to be determined experimentally.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The partition coefficient is usually measured for water/air systems (see Supporting Information 2), but dissolved substances such as minerals, sugar and other organics can exert a high influence on KVOC,L/G [7, 19, 4956]. Hence, KVOC,L/G values for a given medium/air system have to be determined experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…Aprea et al. [55] and Ammari et Schroen [56] showed that the presence of ethanol in the aqueous phase increases KEA,L/G; ethanol obviously heightens the ester solubility in water. This observation is important since ethanol may emerge as a by‐product during cultivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that the partition coefficient is strongly dependent of temperature under which the measurement was taken, values are thus not directly comparable. The temperature dependence of partition coefficients can be mathematically modelled using the van 't Hoff equation 41 :…”
Section: Partition Coefficients Of Volatile Esters In Winementioning
confidence: 99%
“…Hence, recent studies are now beginning to characterise some of the more complex interactions underpinning the partitioning of aroma compounds from the bolus during the oral processing pathway [24][25][26][27] . However, like most studies on food, the majority of research on beer examines the influence of ethanol on the partitioning of individual aroma compounds in water/ethanol solutions 28,29 , although one has examined flavour release in a model beer 17 . Furthermore, to the best of the author's knowledge no studies to date have investigated flavour interactions during oral processing in a real beer matrix and, in particular, a non-alcoholic one.…”
mentioning
confidence: 99%